Prospective study of patient satisfaction and postoperative quality of life after laparoscopic colectomy in Japan. Issue 3 (25th April 2016) - Matsumoto, Sumio; Bito, Seiji; Fujii, Shoichi; Inomata, Masashi; Saida, Yoshihisa; Murata, Kohei; Saito, Shuji
Abstract: Introduction: This prospective cohort study was designed to compare the short‐term and intermediate health‐related quality of life of Japanese patients after laparoscopic colectomy (LC) or open colectomy (OC) for colonic cancer. Methods: Seventeen hospitals participated, and 240 colonic cancer patients with T3 or T4 invasion that were estimated as curatively resected were enrolled. Three patients were excluded as ineligible, one patient died suddenly before operation, and one patient was not registered based on the doctor's decision. Therefore, analysis was done on 235 patients who underwent either LC ( n  = 165) or OC ( n  = 70) in accordance with their stated preference. The major outcome scale end‐point was health‐related quality of life as assessed by the 36‐item Short Form Health Survey (Japanese version 2.0). Accessory end‐points were feeling of satisfaction 1 month after operation and recovery time needed to perform normal activities after operation. Observations were performed on enrollment, postoperative day 3, postoperative day 7, discharge day or postoperative month 1, and postoperative month 6. Results: Defecation condition, wound pain score, and abdominal pain score were better in the LC group than in the OC group on postoperative day 7 and in postoperative month 1. Recovery time to normal daily activity took 30 days in the LC group, whereas the OC group needed 44 days. Conclusion: Patients' subjective responses indicated that LC was more beneficial than OC for patients with stage II or III colonic cancer. LC's superiority was seen particularly in the following indicators: (i) health‐related quality of life during early postoperative days; (ii) recovery to normal daily activities; and (iii) defecation after surgery.